2019
DOI: 10.1111/jtxs.12444
|View full text |Cite
|
Sign up to set email alerts
|

A review of the rheological properties of dilute and concentrated food emulsions

Abstract: Rheology is a powerful and versatile analytical tool for providing information about changes in the composition, structure, and interactions of food emulsions. Moreover, an understanding of emulsion rheology is essential for designing efficient food processing operations and emulsion‐based foods with the desired physicochemical, sensory, and nutritional attributes, such as appearance, texture, flavor, shelf life, and bioavailability. This article provides a brief overview of the current understanding of food e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
66
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(72 citation statements)
references
References 75 publications
4
66
0
2
Order By: Relevance
“…Rheological properties refer to the deformation and flow properties of a substance under external forces. The rheological properties of foods influence their processability, texture, mouthfeel, and shelf life . The main factors affecting the rheological properties of foods were temperature, processing methods, and food ingredients .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rheological properties refer to the deformation and flow properties of a substance under external forces. The rheological properties of foods influence their processability, texture, mouthfeel, and shelf life . The main factors affecting the rheological properties of foods were temperature, processing methods, and food ingredients .…”
Section: Introductionmentioning
confidence: 99%
“…The rheological properties of foods influence their processability, texture, mouthfeel, and shelf life . The main factors affecting the rheological properties of foods were temperature, processing methods, and food ingredients . As the main ingredient of starch‐based foods, it was reported that the granular swelling of starches were significantly related to the rheological properties of starch‐based foods .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In (b) a larger number of cores (N = 19), each of diameter D i = 20 lattice sites, is included within a circular drop, of diameter D O = 136 lattice sites, immersed in a further fluid. In both cases, the area fraction A f = N πR 2 i /πR 2 O occupied by the cores is approximately 0.4, considerably below the close packing limit (∼ 0.74), but sufficiently high to be far from the diluted regime and well within the concentrated one [49]. Such emulsions are initially relaxed towards a nearequilibrium state, and afterwards a symmetric shear is applied, by moving the top wall along the positive y-axis with velocity v w and the bottom one along the opposite direction with velocity −v w .…”
Section: B Numerical Detailsmentioning
confidence: 88%
“…Articles in this issue are invited contributions from some well‐established researchers in the field. A review on the rheological properties of food emulsions deals with the fundamental causes of food texture (Zhu, Gao, Liu, Zou, & McClements, ). Extensional rheology adds a new dimension to food rheology research (Surber, Jaros, & Rohm, ).…”
mentioning
confidence: 99%